1994
DOI: 10.1128/iai.62.7.2834-2842.1994
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of a Candida albicans fimbrial adhesin

Abstract: Candida albicans is the primary etiologic agent of candidiasis, a disease that can vary from superficial mucosal lesions to life-threatening systemic or disseminated diseases. Strains of C. albicans have been reported to possess long, thin filamentous protein cell surface appendages termed fimbriae (R. B. Gardiner, M. Canton, and A. W. Day, Bot. Gaz. 143:534-541, 1982). These fimbriae were isolated, purified, and partially characterized. The major structural subunit of the fimbriae is a glycoprotein which cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 49 publications
2
46
0
2
Order By: Relevance
“…Opportunistic pathogens such as P. aeruginosa, a Gram-negative bacterium, and C. albicans, a dimorphic yeast, employ several distinct adhesins to mediate attachment to host epithelial cells (Prince, 1992;Irvin, 1993;Cutler, 1991;Hostetter, 1994). P. aeruginosa and C. albicans can utilize long flexible filaments termed a pilus and a fimbria, respectively, to mediate their adherence to epithelial cell surfaces (Paranchych and Frost, 1979;Yu et al, 1994a). Pili and fimbriae mediating the attachment of pathogens to the surfaces of the host have been described previously (Irvin, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Opportunistic pathogens such as P. aeruginosa, a Gram-negative bacterium, and C. albicans, a dimorphic yeast, employ several distinct adhesins to mediate attachment to host epithelial cells (Prince, 1992;Irvin, 1993;Cutler, 1991;Hostetter, 1994). P. aeruginosa and C. albicans can utilize long flexible filaments termed a pilus and a fimbria, respectively, to mediate their adherence to epithelial cell surfaces (Paranchych and Frost, 1979;Yu et al, 1994a). Pili and fimbriae mediating the attachment of pathogens to the surfaces of the host have been described previously (Irvin, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Although the adhesin is located on the structural subunit of the PAK pilus, it has been shown that the carboxy-terminal region of the PAK pilin is only exposed at the tip of the pilus where receptor binding occurs (Irvin, 1993;Lee et al, 1994). The C. albicans fimbrial adhesin was first described by Irvin and co-workers (Yu et al, 1994a). The major fimbrial subunit of the C. albicans fimbria is a 66 kDa protein that is highly glycosylated (85% of the molecular mass consists of carbohydrate, primarily D-mannose residues).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations